Work-Life Balance: An Inhibiting or Supporting Employee Engagement on Performance? - Damanik, Patricia Nia Sari (Journal Of Management Analytical and Solution (JoMAS), 2025)
In an increasingly competitive business environment, employee engagement has become a crucial factor in determining the success of an organization. Employees who are actively engaged in their work demonstrate higher levels of productivity, stronger innovation, and greater loyalty to the organization. However, the main challenge currently faced is how to ensure that employee engagement can effectively improve performance. One of the factors that can moderate this relationship is work-life balance, which plays an important role in maintaining employee well-being while also improving employee performance at the North Sumatra Provincial Statistics Office (BPS). This study explores the role of work-life balance as a moderating variable that affects employee engagement on performance using a descriptive quantitative approach. The research population consists of 111 employees of the North Sumatra Provincial Statistics Office using a saturated sampling technique. Data collection techniques were carried out through questionnaires and structured interviews. Data were analyzed using descriptive analysis, reliability and validity tests, as well as Partial Least Squares Structural Equation Modeling (PLS-SEM). The research results prove that employee engagement has a positive and significant impact on employee performance. However, work-life balance hinders the impact of employee engagement on employee performance.